COMMON PATHOGENETIC MECHANISMS OF ATHEROSCLEROSIS AND OSTEOPOROSIS: ELASTICITY OF ARTERIAL WALL AND MINERAL DENSITY OF THE BONE ACCORDING TO SOME PARAMETERS OF REPLICATION CELL AGEING - I. A. Skripnikova; N. A. Alikhanova; E. S. Abirova (Кардиоваскулярная терапия и профилактика)
The review concerns on the common pathogenetic mechanisms of the atherosclerosis and osteoporosis development, and vessel wall elasticity with the decrease of bone mass and changes in bone metabolism. In addition, the results of clinical trials are studied on the exploration of the interconnection between vessel calcification, vessel rigidity values and endurance of the bone tissue. Presence of the common pathogenetic mechanisms in age-dependent diseases with the same molecular markers and serious genetic determination of mineral bone density and vessel calcification creates preterm for the search for common cell markers of early vessel and mone tissue ageing. As the clinical evaluation of the ageing and age-dependent diseases is more linked with the specific problems of their asymptomatic course, during modern period investigators are at most concerned with various informative biomarkers of ageing and the risk of development and prognosis of the diseases’ outcomes. As the role of such common cell markers, which are easy to study in blood leucocytes, the telomeres (length) pretend and telomerase activity.